THE STUDY OF CONSUMER BEHAVIOR ON EYEBROW EMBROIDERY SERVICE WITH JAKARTA FEMALE OFFICE WORKER AS A TARGET MARKET FOR X-THRILL SALON - Christy, Ayu; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2016)
Abstract -- On these couple years, eyebrow embroidery becomes trends on Indonesian celebrity. People start to follow the trends. Eyebrow embroidery starts easier to be accepted. Nowadays, female office workers get more concern about appearance. They also need time efficiency. X-Thrill Salon has consideration that female office workers become a great potential market for eyebrow embroidery. The purpose of this thesis is to study the consumer behavior on eyebrow embroidery service with Jakarta female office worker as target market for X-Thrill Salon. The marketing concept states that, to be successful, a company must understand the needs of specific groups of consumers such as target markets and then satisfy these needs more effectively than the competitor. The satisfaction of consumer needs is delivered in the form of marketing mix. Marketers who have a thorough understanding of the consumer decision-making process are likely to design products or services, establish prices, select distribution outlets, and design promotional message that will favorably influence consumer purchase decisions. The result of this thesis is expected becomes guidelines on formulating future marketing strategy for the business.Â Keywords:Â  consumer behavior, eyebrow embroidery, female office worker.